Effects of Lean Production on Supply Chain Performance in the Automotive Industry in Kenya - Wambi, Rono Ronald; Wambi, Rono Ronald (IJRDO - Journal of Applied Management Science, 2016)
Businesses of all sizes can use the principles of lean enterprise to help eliminate waste, reduce costs and boost productivity. The benefits of achieving process and quality improvements in the workplace are open to private and public companies across all sectors, including areas such as commerce and healthcare alongside traditional industry employers. The core idea is to maximize customer value while minimizing waste. Simply, lean means creating more value for customers with fewer resources. The objective of this study was to determine the effects of lean production on supply chain management. The study will be limited to Simba colt motors in Nairobi, Kenya. This study will adopted a descriptive survey design.The target population